2016
DOI: 10.1165/rcmb.2016-0042oc
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Lung Host Defense in Murine Obesity Models. Insights into Neutrophil Function

Abstract: We have shown that obesity-associated attenuation of murine acute lung injury is driven, in part, by blunted neutrophil chemotaxis, yet differences were noted between the two models of obesity studied. We hypothesized that obesity-associated impairment of multiple neutrophil functions contributes to increased risk for respiratory infection but that such impairments may vary between murine models of obesity. We examined the most commonly used murine obesity models (diet-induced obesity, db/db, CPE fat/fat , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 64 publications
1
36
0
1
Order By: Relevance
“…Given the noted hyperleptinemia-associated defects in neutrophil chemotaxis, and the witnessed impairment in airspace neutrophilia seen in hyperleptinemic mice after LPS exposure, it is interesting that BAL neutrophil levels in lean hyperleptinemic mice at 48 hours after K. pneumoniae infection were found to be similar to those seen in the infected control mice. We have recently shown that a similar phenomenon occurs in diet-induced obese mice after K. pneumoniae infection, in which BAL neutrophil levels are also similar compared with lean controls (56) despite finding impaired airspace neutrophilia following LPS in the obese mice. This parity in airspace neutrophil levels may reflect a compensatory response to worsening infection in the mice with failed bacterial clearance, such that additional neutrophil recruitment signals are released and neutrophils are recruited, though less effectively, as we have previously shown to be the case in obese db/db mice (17).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Given the noted hyperleptinemia-associated defects in neutrophil chemotaxis, and the witnessed impairment in airspace neutrophilia seen in hyperleptinemic mice after LPS exposure, it is interesting that BAL neutrophil levels in lean hyperleptinemic mice at 48 hours after K. pneumoniae infection were found to be similar to those seen in the infected control mice. We have recently shown that a similar phenomenon occurs in diet-induced obese mice after K. pneumoniae infection, in which BAL neutrophil levels are also similar compared with lean controls (56) despite finding impaired airspace neutrophilia following LPS in the obese mice. This parity in airspace neutrophil levels may reflect a compensatory response to worsening infection in the mice with failed bacterial clearance, such that additional neutrophil recruitment signals are released and neutrophils are recruited, though less effectively, as we have previously shown to be the case in obese db/db mice (17).…”
Section: Discussionmentioning
confidence: 70%
“…We have previously shown that neutrophils isolated from uninjured obese mice demonstrate functional defects, including impaired chemotaxis at baseline (23, 56), that likely attenuate neutrophil recruitment to the lung early in the course of infection and contribute to the failure to contain infection in these mice. In the current study, we demonstrate similar functional defects in neutrophils isolated from lean hyperleptinemic mice, indicating that such defects may contribute to the failure to contain bacterial pneumonia in hyperleptinemic mice, as well, and further suggesting that the hyperleptinemic state itself may contribute to these defects in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Mice on a high fat diet exhibit increased airway hyperactivity due to an expansion of ILC3-like cells that produce IL-17A in the lung in response to IL-1β released from M1 macrophages 130 . Mice with obesity show a reduced ability to control bacterial pneumonia 131 , and impaired antimicrobial host defenses may be a consequence of reduced neutrophil recruitment into the alveoli, which is also reduced during airway injury and LPS challenge in obese mice 129 . Interestingly, during mouse H1N1 IAV infections, obesity is associated with increased lung pathology and impaired tissue repair without altered viral titers, suggesting that disease tolerance may be additionally compromised in obese individuals 132 .…”
Section: Modifiers Of Respiratory Immunitymentioning
confidence: 99%
“…We must consider the possibility that obesity may alter ARDS pathogenesis by "priming" the lung for inflammatory insult and amplifying the early inflammatory response (thus lowering the threshold to initiate ARDS), while at the same time accelerating a subsequent transition to the recovery phase. How obesity may change the "inflammatory twitch" of the lung (35) is only beginning to be understood, but on the basis of recent mouse modeling, this appears to include both baseline pulmonary vascular "priming" (34) and neutrophil functional impairment (28,36,37), as well as other effects of elements of the metabolic syndrome, including hyperglycemia (29,36), dyslipidemia (28,36,37), hypoadiponectinemia (34,38), and hyperleptinemia (39). For example, recent studies by Shah and colleagues (34), examining several mouse strains that vary in their susceptibility to diabetes in a dietinduced obesity (DIO) model, have highlighted the complex interplay between glucose intolerance and lung injury.…”
Section: Acute Lung Injury and Ardsmentioning
confidence: 99%
“…As might be anticipated from the above-noted findings in obese mouse models of sterile lung injury and inflammation, the pulmonary immune response to infectious pathogens also appears deranged. Pulmonary bacterial clearance and containment appear to be impaired in several obese mouse models, and studies have suggested a role for both neutrophil and macrophage dysfunction in this setting (36,48). Despite likely impaired bacterial containment, the majority of studies have found little or no obesity-associated increase in lung viral titer in influenza infection, but instead demonstrate an overexuberant inflammatory response and accompanying lung injury (44)(45)(46).…”
Section: Severity Of Influenza a Infection Have Beenmentioning
confidence: 99%